Penggunaan Bahasa Daerah pada Buku Bacaan Siswa Terbitan Kemdikbud - Aisyah Nur Fadhilah; Laili Etika Rahmawati (Universitas PGRI Madiun, 2020)
This study aims to identify the use of regional languages in student reading books published by the Ministry of Education and Culture. This type of research is a qualitative descriptive study. The object of research is the local language in the student reading book published by the Ministry of Education and Culture entitled